A Study on Problems in the Insurance Repository System in India - Pius, Ashish C; Velmurugan, R. (Indian Journal of Information Sources and Services, 2024)
This section discusses the problems of the insurance repository system and it is possible to state that the situation is quite chaotic here. Due to the availability of many repositories in the industry, policyholders are confused and the emergence of repository services distorts the insurers-policyholders nexus. Further, the majority of the policyholders have low computer literacy which extends the problem as far as the adoption of the repository services is concerned and also increases the possibility of exploiting the policyholder information. But when arrangements are made to try and bring the services closer to ensure that they are availed to all the various policyholders of the repository services, it is realized that many of the life insurance firms do not encourage the policyholders through active marketing. And, it contributes to the other issue which makes the policyholders’ attitude towards the repository system not highly positive. Promoting the use of the repository system has also been lacking tangent arising from the interface initiates that copy with the hands of the regulatory bodies such as IRDA. In the context of this research, system barriers, including network availability bear more difficulty in being solved, hence resulting in higher variability in as well as levels and patterns of use of the repository system compared to consolidated groups like the CPRP. These complex challenges underscore the need to come up with suitable and feasible interventions to address the issues that have characterized the insurance repository system, with the view to making it functional for all the targeted users and other stakeholders.